2021
DOI: 10.1515/chem-2021-0194
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of γ-Fe2O3 from copper ore tailings by magnetization roasting and magnetic separation

Abstract: To comprehensively reuse copper ore tailings, the recovery of γ-Fe2O3 from magnetic roasted slag after sulfur release from copper ore tailings followed by magnetic separation is performed. In this work, after analysis of chemical composition and mineralogical phase composition, the effects of parameters in both magnetization roasting and magnetic separation process with respect to roasting temperature, residence time, airflow, particle size distribution, magnetic field intensity, and the ratio of sodium dodecy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In order to actively respond to the call for comprehensive utilization of COT, a systematic approach for the successive release of sulfur and the recovery of iron by a linear route, including oxidation roasting and magnetic separation, were investigated in our previous study. [2] We showed that sulfur could be released in a first step, followed by iron recovery. However, this process generates residues after sulfur release and iron recovery.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In order to actively respond to the call for comprehensive utilization of COT, a systematic approach for the successive release of sulfur and the recovery of iron by a linear route, including oxidation roasting and magnetic separation, were investigated in our previous study. [2] We showed that sulfur could be released in a first step, followed by iron recovery. However, this process generates residues after sulfur release and iron recovery.…”
Section: Introductionmentioning
confidence: 93%
“…Residues collected from a previous study have been used as raw material in this study. [2] The residues were produced successively through a series of treatments including oxidizing roasting, sulfur release and magnetic separation of the copper ore tailings in optimum conditions. The residues as samples were grounded into powders below 200 meshes and dried at 105 � 2 °C for 24 h. The main chemical components with more than 0.4 wt.% are shown in Table 1 Based on the CaOÀ FeOÀ SiO 2 phase diagram [25] shown in Figure 1, three groups of formulations were designed and labelled as BZ-0 wt.%, BZ-5 wt.% and BZ-10 wt.%.…”
Section: Experimental Section Materials Preparation and Devicesmentioning
confidence: 99%
See 1 more Smart Citation